2005
DOI: 10.1038/sj.gt.3302558
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral transduction of IL-7Rα into IL-7Rα−/− bone marrow progenitors: correction of lymphoid deficiency and induction of neutrophilia

Abstract: Defects in the gene for the IL-7 receptor (R) a chain are one cause of severe combined immunodeficiency disease (SCID) based on a strict requirement for IL-7 in T lymphoid development and survival. We tested the feasibility and potentially undesirable consequences of IL-7Ra gene transfer as a therapy for this genetic defect. The murine IL-7Ra gene was introduced into IL-7Ra À/À bone marrow progenitors using retrovirus and transplanted into Rag À/À recipient mice. Both ab and gd T cells were reconstituted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…splenomegaly resulting from neutrophilia. 10 Consistent with this report, transduced WT appeared to induce some degree of increase in myeloid fraction and neutrophilia in PB and SP compared with that of mock increase of myeloid fraction and neutrophilia in PB (supplemental Figure 4). Importantly, the magnitude was quite different, as we could not find a statistically significant difference of SP weight in mock and WT (n 5 4 each; P 5 .61, 1-way analysis of variance; supplemental Figure 3C).…”
Section: Resultssupporting
confidence: 78%
“…splenomegaly resulting from neutrophilia. 10 Consistent with this report, transduced WT appeared to induce some degree of increase in myeloid fraction and neutrophilia in PB and SP compared with that of mock increase of myeloid fraction and neutrophilia in PB (supplemental Figure 4). Importantly, the magnitude was quite different, as we could not find a statistically significant difference of SP weight in mock and WT (n 5 4 each; P 5 .61, 1-way analysis of variance; supplemental Figure 3C).…”
Section: Resultssupporting
confidence: 78%
“…Despite the mature neutrophils not having a functional IL-7 receptor (Girard and Beaulieu 1997), it has been reported that mielopoietic precursors could have (Grzegorzewski et al 1994). An increase of neutrophils in lymphopenic mice has also been reported after recombinant rh-IL-7 administration (Jiang et al 2005;Aiello et al 2007). The increase of IL-7 levels induced by a lymphopenic status is well known.…”
Section: Discussionmentioning
confidence: 86%
“…This suggests that the intracellular domains and signaling pathways, diverse as they are, may be roughly equivalent in bone marrow cells in terms of inducing survival and proliferation. From these bone marrow progenitors, we have previously characterized the cell types generated by ectopic expression of WT IL-7R to be predominately of the myeloid lineage (26). The cell types that arose in culture from progenitors harboring chimeric receptors are shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, we recently showed that IL-7R, which normally functions in the lymphocyte lineage, can also induce myelopoiesis when ectopically expressed in the myeloid lineage (26), perhaps mimicking a myeloid factor such as G-CSF. In this study, we also observed a myelopoietic effect (data not shown).…”
Section: Discussionmentioning
confidence: 99%